Validity and Practicality of the Ethnoscience-Based Design Thinking E-book - Diah Kartika Sari; Yenny Anwar; Eka Ad'hiya; Sofia; Rodi Edi (Postgraduate, University of Mataram, 2023)
Design thinking is an innovation methodology that combines skills, processes and mindset. Design thinking is becoming increasingly popular in education as a way to encourage students to think critically, collaborate effectively, and develop innovative solutions to complex problems. Teachers and students can solve wicked problems creatively using design thinking. This research aims to determine the validity and practicality of an ethnoscience-based design thinking e-book. This research was conducted using walkthroughs and questionnaires. Validation data was analyzed using Cohen's Kappa while practicality data was analyzed using percentages. The results show that the ethnoscience-based design thinking textbook that was developed was said to be valid in aspects of design, systematics, substance and writing style. The textbooks being developed are also said to be very practical in terms of design, language, material and interest aspects.